Habitation of Congregational Prayer as a Formation of Good Character at Madrasah Tsanawiyah Al Huda Blora - Masngut, Masngut; Romelah, Romelah; Mardiana, Dina (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The purpose of this study was to describe the habit of congregational prayer in forming the noble character of students at Madrasah Tsanawiyah (MTs) Al Huda Kunduran, Blora Regency. This research approach uses qualitative with a case study type, located at MTs Al Huda Kunduran, Blora Regency. The informants in this study were the Principal (D) 2 Islamic Religious Education teachers (S and AS) because Islamic Religious Education teachers have a central role in the habit of congregational prayer in the formation of noble character and are responsible for guiding students in worship practices, as well as acting as role models in forming Islamic character, four students consisting of 2 males (BJJ and UZ) and two females (US and NF). Data collection techniques used observation, interviews, and documentation; data analysis techniques used the theory of Miles, Huberman, and Saldana. The study results showed that the habituating congregational prayer program had run well and positively impacted student character formation, especially regarding discipline, togetherness, and obedience to religious teachings. As a result, the habituating congregational dhuha and dzuhur prayers at MTs Al Huda Kunduran Blora is a strategic step in building students' morals through internalizing the values ​​of discipline, spirituality, and togetherness. This program emphasizes that habituation and supervision must be carried out consistently so that the benefits can last a long time. It also strengthens the role of teachers as models in shaping students' characters.